2020
DOI: 10.1039/c9cp06942a
|View full text |Cite
|
Sign up to set email alerts
|

Novel two-dimensional silicon–carbon binaries by crystal structure prediction

Abstract: A theoretical study of the phase diagram of two-dimensional silicon–carbon binaries unveils a large variety of electronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…A multitude of two-dimensional networks consisting of Si-C rings of various sizes (3–9) were observed, which agreed with analogous ring structures in the pure C-system, many of which had also been found in a number of other exploration studies [67,68]. All the atoms in these structures had only two or three neighbour atoms, and thus, the bonds should be considered as sp- and sp 2 -hybridized bonds.…”
Section: Examplessupporting
confidence: 83%
See 1 more Smart Citation
“…A multitude of two-dimensional networks consisting of Si-C rings of various sizes (3–9) were observed, which agreed with analogous ring structures in the pure C-system, many of which had also been found in a number of other exploration studies [67,68]. All the atoms in these structures had only two or three neighbour atoms, and thus, the bonds should be considered as sp- and sp 2 -hybridized bonds.…”
Section: Examplessupporting
confidence: 83%
“…Since it has become possible to generate free-standing monolayers of graphene, the prediction of alternative structures in monolayers of carbon and related compounds has become a topic of interest [56,[66][67][68][69][70]. As an example, we discuss here the prediction of stable local minimum structures in two dimensions in the Si/C system using variable periodic simulation cells [56,70].…”
Section: (C) Pure Two-dimensional Systemsmentioning
confidence: 99%
“…It has been demonstrated that the electronic and optical features of g-SiC and g-GeC nanosheets can be effectively tuned by introducing defects or adatoms, modifying the stacking sequence, adjusting the thickness, and applying strain or an external electric field. Numerous experimental and theoretical investigations have addressed the functionalization of g-SiC and g-GeC nanosheets for optoelectronic devices, ,,,, integrated nanodevices, and metal-free electrocatalysts . Since photovoltaic applications are hindered by wide and indirect band gaps, extensive research efforts have been made toward predicting new 2D silicon carbides. For example, based on the density functional theory, Li et al and Zhou et al have reported metallic silagraphene and semiconducting siligraphene (g-SiC 2 ) with a direct band gap of 1.09 eV, respectively. Li et al, Shi et al, and Borlido et al have comprehensively studied the stabilities and electronic properties of monolayer Si x C y for different stoichiometric compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Since photovoltaic applications are hindered by wide and indirect band gaps, extensive research efforts have been made toward predicting new 2D silicon carbides. For example, based on the density functional theory, Li et al and Zhou et al have reported metallic silagraphene and semiconducting siligraphene (g-SiC 2 ) with a direct band gap of 1.09 eV, respectively. Li et al, Shi et al, and Borlido et al have comprehensively studied the stabilities and electronic properties of monolayer Si x C y for different stoichiometric compositions. On the other hand, so far no additional stable structures of 2D germanium carbides have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous 2D silicon carbide compounds were also fabricated and proposed, for instance, experimentally synthesized graphitic SiC [4][5][6], planar SiC2 silagraphene with tetracoordinated Si [23], planar graphitic SiC2 [24], carbon-rich SiC3 [25], g-SiC2 [24], pt-SiC2 [23], SiC6-SW [26], SiC2-b [26], SiC2-p [26], quasi-planar tetragonal SiC and SiC2 [27] , penta-SiC2 [28], a series of silagraphyne [27], silicon-rich Si3C [26], and recently reported tetrahex SiC [29]. These 2D nanostructures exhibit either metallic (semimetal) or semiconducting with a finite band gap.…”
Section: Introductionmentioning
confidence: 99%